Methods of estimation of reference crop evapotranspiration for the conditions of northeastern semi-arid, Brazil - Cavalcante Junior, Edmilson Gomes (2011)
The objective of this work was to evaluate methods of estimation of reference crop evapotranspiration (ETo) in conditions of low and high air relative humidity, using the Penman Monteith-FAO 56 method as reference. Data from the period between January 2002 and June 2008 were obtained from a conventional meteorological station at Semiarid Federal Rural University, in Mossoró, RN, Brazil. Evaluation of methods was made by means of the precision index “r”, accuracy “d”, and of confidence or performance “c”. Methods Kimberly-Penman 1982, Kimberly-Penman 1972, Benevides-Lopez 1970 and Hargreaves-Samani 1985 obtained an important improvement in their performance when high air relative humidity conditions were considered (UR > 70%), compared to low air relative humidity conditions (UR < 70%). Equations of Makkink 1957 and Hamon 1961 underestimated ETo in both periods, and the method Penman modified-FAO24 showed tendency to overestimate the reference method. Methods Penman 1948, FAO24-Radiation, FAO24-Blaney-Criddle and Frere-Popov presented the higher performance among the evaluated methods.